Pemaknaan Nilai Kebangsaan di Perguruan Tinggi sebagai Strategi Penguatan Identitas Generasi Muda: Studi Fenomenologi Interpretatif - Setyo Budi Takarina; Hastangka Hastangka (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to reconstruct national values in higher education as a strategic effort to strengthen the identity of the younger generation. The study focuses on understanding how university students interpret the commemoration of National Awakening Day, how reflective learning contributes to the formation of national identity, and how these interpretations can inform the development of national-value–based learning in higher education.Methods – The study employs a qualitative approach using Interpretative Phenomenological Analysis (IPA). Data were collected from written reflective narratives produced by 22 Civic Education students at a public university in Indonesia in the year 2024/2025. The analysis proceeded through repeated reading of the reflections to capture the context of personal meaning-making, followed by thematic interpretation to identify experiential patterns, and concluded with integrative analysis to understand the dynamics through which students construct and negotiate national values.Findings – The findings show that students’ understanding of National Awakening Day is shaped by intertwined mechanisms. The historic legacy of the national movement becomes an important cognitive foundation that helps students reconnect with ideas of unity and collective struggle. Reflective learning in the classroom serves as a mediating space where national identity is reinterpreted in relation to students’ personal, cultural, and academic experiences. Research Implications – The study highlights relevant implications for higher education, particularly the importance of integrating structured reflective activities into civic and character education courses. Such approaches can help students connect historical national events with contemporary realities and foster more meaningful internalization of national values within the university context.